THREADS OF TRANSFORMATION: ALEXANDR FEINBERG’S ARTISTIC TAPESTRY - Shukurova Visola; Jamilya Abduganieva (Galaxy International Interdisciplinary Research Journal, 2024)
Alexandr Feinberg, a renowned poet from Uzbekistan, weaves intricate threads of transformation through his poetic tapestry. This article delves into the thematic and stylistic elements that define Feinberg’s poetry, exploring how his works serve as a catalyst for personal and societal change. Through an analysis of Feinberg’s exploration of identity, memory, and resilience, this article illuminates the transformative power of art in shaping individual and collective consciousness.